Lock every door [compact disc, unabridged] : a novel - Sager, Riley (Penguin Audio, 2019)
No visitors. No nights spent away from the apartment. No disturbing the other residents, all of whom are rich or famous or both. These are the only rules for Jules Larsen's new job as an apartment sitter at the Bartholomew, one of Manhattan's most high-profile and mysterious buildings. Recently heartbroken and just plain broke, Jules is taken in by the splendor of her surroundings and accepts the terms, ready to leave her past life behind. As she gets to know the residents and staff of the Bartholomew, Jules finds herself drawn to fellow apartment sitter Ingrid, who comfortingly, disturbingly reminds her of the sister she lost eight years ago. When Ingrid confides that the Bartholomew is not what it seems and the dark history hidden beneath its gleaming facade is starting to frighten her, Jules brushes it off as a harmless ghost story, until the next day, when Ingrid disappears. Searching for the truth about Ingrid's disappearance, Jules digs deeper into the Bartholomew's dark past.